FACTORS ASSOCIATED WITH PHYSICAL ACTIVITY AMID AMBIENT PM 2.5 AIR POLLUTION AMONG ADOLESCENTS IN SUPHANBURI PROVINCE, THAILAND: A CROSS-SECTIONAL STUDY - Waenkaew, Katthaleeya; Laisuwannachart, Panjarut; Sejati, Putri Eka; Zaw, Kaung; Istighosah, Nining; Kehanak, Srisurang; Bunsiriluck, Supaporn; Thongnak, Thanittha; Duangchinda, Aittiphol (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
This study investigates the influence of Particulate Matter 2.5 (PM2.5) air pollution on adolescent engagement in physical activities, which are critical for their physical and social development. Utilizing the PRECEDE framework, this cross-sectional study identifies key factors affecting adolescents' willingness to participate in physical activities during periods of high PM2.5 concentration. A total of 227 adolescents completed an online self-administered questionnaire. Descriptive statistics and Chi-Square tests were employed for data analysis, with statistical significance set at p < .05. The analysis revealed that two factors—academic discipline (χ² = 12.10, p = .033) and knowledge of safe physical activity during elevated PM2.5 periods (χ² = 13.91, p = .000)—significantly influence adolescents' engagement in outdoor activities despite pollution risks. These findings suggest that adolescents with certain educational backgrounds and greater knowledge of protective measures are more likely to remain active during high pollution episodes. This study underscores the need for tailored educational interventions to foster safe physical activity practices among adolescents in polluted environments. The results contribute to understanding how educational and knowledge-based factors can mitigate the adverse effects of PM2.5 pollution on adolescent lifestyles, offering insights for policy development aimed at promoting health-conscious behaviors in urban settings with elevated pollution levels.